Finite element analysis of nanoindentation pile-up and correction of projected contact area - Jaroslav Kovář; Vladimír Fuis; Radim Čtvrtlík; Jan Tomáštík (Acta Polytechnica CTU Proceedings)
This paper deals with the pile-up phenomenon that can occur during nanoindentation. Finite Element (FE) simulation of X5CrNiCuNb16-4 steel nanoindentation with pyramidal Berkovich indenter was done, and stress and strain beneath the indenter leading to pile-up behavior were analyzed in detail. Pile-up also influences the projected contact area, which should be corrected to include the pile-up into the Oliver-Pharr analysis. Accurate calculation of the projected contact area requires knowledge of its boundary. Few methods of boundary approximation were used, including approximation by the triangle and the semi-ellipse. For more precise approximation, the expression for parabolical approximation was derived. These methods were compared with the projected contact area calculated by finite element method. The most precise results were obtained using semi-elliptical and parabolical correction, which can be used for the determination of the projected contact area and its boundary.